The Impact of Using the TikTok Application on Social Interactions of Teenagers in Pabuaran Cibadak Village - Nazwan, Haryati; Wulandari, Maudi (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2024)
The rapid development of communication technology has had an impact on people's lives, especially teenagers. In the era of technology, one of the developments in human civilization today is creativity and communication through social media. Through social media, they can get to know and talk to new people they know. One of the most popular social media sites in Indonesia currently is the Tiktok application.This research uses qualitative methods to obtain data and explain phenomena by direct observation. Qualitative methods are methods that tend to use analysis and are descriptive. The results of this research show that: 1. The use of the TikTok application by teenagers in Pabuaran Cibadak Village can influence their social interactions. 2. The motive for using the TikTok application by teenagers in Pabuaran Cibadak Village is because of invitations from their own friends and curiosity about trending applications. 3. The positive impact of using the TikTok application is skill development